Vaccination with recombinant Toxoplasma gondii bradyzoite-formation deficient 1 (rTgBFD1) antigen provides partial protective immunity against chronic T. gondii infection - Tian, Xiaowei; Yang, Zhenke; Wan, Guangmin; Xie, Tong; Wang, Meng; Sun, Hanqi; Mei, Xuefang; Zhang, Zhenchao; Li, Xiangrui; Wang, Shuai (Frontiers in Veterinary Science, 2022)
As an apicomplexan pathogen, Toxoplasma gondii still remains a major threat to public health and requires specific attention. In fact, positive attempts to identify more effective antigens to provide protection are important to control toxoplasmosis. Latest scientific advances in T. gondii study hint at the probability of the T. gondii bradyzoite-formation deficient 1 (TgBFD1) as an ideal vaccine candidate, since this molecule plays a critical role in regulating the chronic infection of T. gondii. Thus, BALB/c mouse models of acute and chronic T. gondii infections were used to evaluate the TgBFD1 protection efficacy in this study. Before conducting animal trials, antigen analysis of TgBFD1 were performed using DNAstar software and Western blots. The preliminary results suggested that TgBFD1 should be a potent immunogen. Then, this conclusion is confirmed by ELISA assays. After immunization with rTgBFD1, high levels of specific IgG, IgG1, IgG2a and cytokines (Interferon γ and interleukin 10) were observed, indicating that TgBFD1 could induce strong protective antibody responses. While TgBFD1-specific IgG antibodies were measurable in vaccinated mice, no protection was observed in the acute T. gondii infection (RH strain) assay. However, there still shows a noticeable decrease in brain cysts counts of immunized mice compared with negative controls in the latent T. gondii infection (PRU strain) assay. Taken together, these results indicated that rTgBFD1 had the remarkable ability to elicit both humoral and cellular immune responses and could provide partial protective immunity against chronic T. gondii infection.